Limitations On Insurance Subrogation Rights And Carrier Responsibilities: Case Analysis Of Decision 452/PDT/2021/PT.DKI In Sea Freight - Jaya Irianto Purba; Hulman Panjaitan; Gindo L Tobing (Jurnal Ekonomi, 2024)
This research aims to analyze the carrier's responsibilities in sea transportation, as well as evaluate the suitability of the Panel of Judges' legal considerations in the case between PT. Asuransi FPG Indonesia and PT. Pelayaran Tempuran Emas related to subrogation in insurance and responsibility of sea carriers. The research method used is normative descriptive analytical using primary, secondary and tertiary data. Various regulations that are used as references include Law no. 40 of 2014 concerning Insurance, Law no. 17 of 2008 concerning Shipping, Government Regulation no. 20 of 2010 concerning Water Transport (PP No. 20/2010), Government Regulation no. 51 of 2002 concerning Shipping (PP No. 51/2002), and Minister of Transportation Regulation No. 76 of 2017 concerning the Organization and Working Procedures of the Shipping Court. This research analyzes Decision Number 415/Pdt.G/2019/Pn. Jkt. Utr. regarding the dispute between PT. FPG Indonesia InsuranceJaya Iriantoin vain against PT. The Golden Tempuran Voyage, which was later canceled on appeal through Decision Number 452/PDT/2021/PT.DKI. The decision stated that the Plaintiff was not entitled to receive compensation payments that had been paid to PT RAPP. The conclusion highlights the responsibility of the carrier in maintaining the safety of goods, as well as the importance of the right of subrogation in insurance law, although there is uncertainty in the legal interpretation used.